Characterisation and Manipulation of Transition Metal Dichalcogenides via Atomic Force Microscopy - O'Neill, Katie (Trinity College Dublin. School of Physics. Discipline of Physics, 2022)
Scanning probe microscopy (SPM) has revolutionised nanotechnology and allowed the study and manipulation of materials at the nanoscale, making it ideal for the study of solid-state physics and semiconductor technologies. Atomic force microscopy (AFM) and scanning probe lithography (SPL) can be used as a toolbox for mechanical treatments of various surfaces including polymers, metals and semiconductors. In recent years, two-dimensional (2D) layered materials, such as graphene and transition metal dichalcogenides (TMDs), have been heavily studied due to their high potential for use in a wide range of future nanoelectronic devices. Some semiconducting TMDs, such as MoS2, are known to change their bandgap with decreasing layer thickness. Other TMDs, such as PtSe2, have been shown to develop a band gap, i.e. go from semi-metallic to semiconducting. The first results chapter of this thesis details where one such tool , the technique of nanoshaving, where materials are selectively removed by an AFM tip, is employed to produce nanopatterns of self-assembled monolayers (SAMs) on 2D materials. The materials used are monolayers of TMDs, namely MoS2 and WS2 non-covalently functionalised with a perylene derivative, perylene diimide (PDI). The approach involves rastering an AFM probe across the surface at a controlled increased load in ambient conditions. Due to the strong bond between PDI SAM and TMD, it is found that loads in excess of 1 μN are required to pattern the monolayer. Various pre-defined patterns including a grating pattern with feature sizes below 250 nm are demonstrated, showing the high precision of nanoshaving as an accurate and non-destructive lithographic technique for 2D materials. In addition, non-covalent co-functionalisation of MoS2 is demonstrated using perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA) SAMs on previously nanoshaved areas. Work functions of the shaved heterostructures are also examined using Kelvin probe force microscopy, another SPM-based tool. The second results chapter describes the use of SPL and SPM-based tools with the aim of producing a seamless, self-contacted device by way of suitable material, namely PtSe2. A technique for manipulating TMD layers is explored and developed via nanomachining using AFM, which is used to reduce and control the layer thickness of PtSe2 in the form of thermally assisted converted (TAC) films and mechanically exfoliated (ME) flakes. AFM and SEM results reveal the nanomachining of TAC films to be quite difficult due to the roughness of the films post-selenisation when compared to exfoliated materials. Nevertheless nanomachining TAC films results in thinner, smoother films overall. Machining of pristine Pt channels allows more control over the quantity of nanomachining, and also quality. For comparison with TAC films, electrically contacted ME PtSe2 flakes are nanomachined at loads of 0.8 − 2.7 μN. Raman spectroscopy of the nanomachined area shows more defective/damage material in the remaining layers, which are more easily removed than pristine layers with successive passes of nanomachining at the same loads. This suggests a path for continuous monitoring of device performance with each layer removal down to the monolayer, starting with metallic multi-layers and thinning down to a semiconducting monolayer. This would enable the design of self-contacted devices based on TMDs through the creation of a semiconducting channel via nanomachining with high mobility, low contact resistance and low power. The research undertaken showed how AFM-based mechanical manipulation techniques, namely nanoshaving and nanomachining, can be used to examine and explore TMDs and TMD-based heterostructures, along with complementary spectroscopy techniques. In addition, this work has opened pathways to future studies on the capability of AFM as a toolbox for characterisation of 2D materials as well as SPL and 2D materials/heterostructures.
APPROVED
Keywords: 2D material; transition metal dichalcogenide; atomic force microscopy; nanoshaving; nanomachining; kelvin probe force microscopy; KPFM; surface funtionalisation; perylenes; perylene diimide; PTCDA; MoS2; PtSe2; WS2